<< u mean there isnt any diferent between the first derivative & the

nth

derivative of (sinx)^a?!?!

that one that u said is just for the first derivative, >>

Oops... I totally missed the part where you're asking for the nth

derivative. Let me modify

my answer then:

First, note that for f(x) = (sinx)^a, we have:

f'(x) = a*cosx*(sinx)^(a-1)

f''(x) = a^2*(cosx)^2*(sinx)^(a-2) - a*(sinx)^a

f(3)(x) = a^3*(cosx)^3*(sinx)^(a-3) + 2 a^2 * cosx sinx - a^2 cosx*

(sinx)^(a-1)

...

I'm having trouble finding the pattern, so sorry, I don't have your

answer.